Study on Fundamental Principles and Methodologies of Distribution Network Reconfiguration - Feng Xiaoke; Shen Weiwei; Dong Chunyu; Zeng Jianliang; Shi Jidong; Wang Dongju (Institute of Advanced Engineering and Science, 2014)
Distribution network reconfiguration is not only of great use in controlling and improving power distribution system’s operation environment, but also an essential part of the distribution management system. Thus the research on fundamental principles and methodologies of distribution network reconfiguration is very important and meaningful. This article has suggested the principles of distribution network reconfiguration under circumstances of normal operation and service restoration after faults, and one step further focused on typical algorithms applied in the area including optimal power flow algorithm, branch exchange algorithm, simulated annealing algorithm, artificial neural network algorithm, genetic algorithm and tabu search algorithm. Based on specific comparison and analysis, this article summarized characters of different methodologies and pointed out that alterations still have to be made to derive better solution. DOI : http://dx.doi.org/10.11591/telkomnika.v12i3.4564